Early Canadian Botanical Photography at the Exposition universelle, Paris 1867 - Cull, Brendan (Scientia Canadensis, 2016)
Sites et végétaux du Canada was an early photographic experiment in botanical illustration. Presented at the 1867 Paris exposition, the album’s 35 albumen prints were part of the Canadian displays. The photographs were a collaborative effort between Joseph-Charles Taché, Canada’s Executive-Secretary at the exposition; Louis-Ovide Brunet, a Catholic priest and botany professor at the Université Laval; and Livernois & Cie, a Québec City photography studio. Previous work has considered the album as the aesthetic accomplishment of Jules-Isaïe Benoît dit Livernois, excluding Taché and Brunet from the art historical narrative. In this paper, I consider the album’s political and botanical contexts, and viewership, to more clearly situate the album in the visual culture of early Canadian science. In its representation of Canadian landscapes and native-plant specimens, the album effectively employed photography to present Canada as a centre of cutting-edge scientific investigation.